PERFORMANCE OF CHRYSANTHEMUM (Dendranthema grandiflora) HYBRIDS - K.SUSHMA, K. DHANUMJAYA RAO and (The Journal of Research, PJTSAU, 2017)
An experiment on the evaluation of certain chrysanthemum genotypes was conducted for three consecutive years from 2010 to 2013 at Floricultural Research Station, Hyderabad with an objective of the identification of a suitable variety for the cultivation in Telangana. Fourteen genotypes of chrysanthemum along with check Silper were evaluated and maximum average plant height (58.8 cm), no. of branches/plant (13.2), spray length (32.0 cm) and no. of flowers / spray (32.3) were recorded in PAU-B-43 over check Silper. Highest plant spread (69.5 cm) and diameter of flower (7.9 cm) were recorded in Garden Beauty over control. Minimum no. of days taken to 1st flower bud appearance (36), no. of days taken to 50% flowering (55) were recordedin Yellow Delight over Silper. Average flower weight (3.2 g) was recorded in Raichur over check. Highest no. of flowers/plant (yield) was recorded in winter queen (211) over silper and no. of suckers/plant was recorded maximum in PAU-D-1 (42.7) over control.